The Motivation-Based Promotion of Proactive Control: The Role of Salience Network - Qiao, Lei; Xu, Lei; Che, Xianwei; Zhang, Lijie; Li, Yadan; Xue, Gui; Li, Hong; Chen, Antao (Frontiers in Human Neuroscience, 2018)
It has been shown that reward motivation can facilitate proactive control, a cognitive control mode that is characterized of prior preparation and sustained holding of the goal-relevant information in working memory. However, it remains to be established the neural networks that may be involved in this promotion effect. In this study, participants underwent the AX-Continuous Performance Task (AX-CPT) that measures relative proactive control during functional Magnetic Resonance Imaging (fMRI) scanning. Results showed that the salience network (SN) was engaged in the AX-CPT protocol. Importantly, our data demonstrated that reward modulated the association between task engagement of SN and proactive control, whereby the positive correlation was particularly observed in the reward condition. Moreover, reward modulated task engagement of the SN in a proactive manner, which may contribute to the behavioral proactive performance. Overall, our data suggest the involvement of SN in the reward facilitation effect of proactive control.